Beyond parliamentary ratification: the role of national and subnational parliaments in EU-Mercosur trade negotiations - Theodoro Luciano, Bruno [UNESP]; Junqueira, Cairo Gabriel Borges (Taylor & Francis, 2023)
This article aims to assess how national and subnational parliaments have engaged with recent trade negotiations, by examining how they have been responding to the conclusion of the Association Agreement with the Southern Common Market (Mercosur), agreed in principle in June 2019. It argues that–even though the executives from both sides have reached an initial agreement–national and some subnational parliamentary actors have been playing a key role in the revision and implementation of this comprehensive inter-regional agreement, succeeding in stalling the accord even before its signature and the beginning of the ratification process. Besides, the article unveils major differences between the involvement of EU and Mercosur’s national and subnational parliaments concerning the agreement: while a high level of parliamentary mobilisation was observed in the EU, so far parliamentary involvement has been quite low in the Mercosur side.
Keywords: EU trade policy; EU-Mercosur agreement; national parliaments; parliamentary diplomacy; parliamentary paradiplomacy; subnational parliaments